Cloning the interleukin 1 receptor from human T cells. - Sims, J E (1989)
cDNA clones of the interleukin 1 (IL-1) receptor expressed in a human T-cell clone have been isolated by using a murine IL-1 receptor cDNA as a probe. The human and mouse receptors show a high degree of sequence conservation. Both are integral membrane proteins possessing a single membrane-spanning segment. Similar to the mouse receptor, the human IL-1 receptor contains a large cytoplasmic region and an extracellular, IL-1 binding portion composed of three immunoglobulin-like domains. When transfected into COS cells, the human IL-1 receptor cDNA clone leads to expression of two different affinity classes of receptors, with Ka values indistinguishable from those determined for IL-1 receptors in the original T-cell clone. An IL-1 receptor expressed in human dermal fibroblasts has also been cloned and sequenced and found to be identical to the IL-1 receptor expressed in T cells.